Quasi-three-level Nd:GdYNbO4 927 nm laser under 879 nm laser diode pumping. (12th June 2018) - Yan, Renpeng; Zhao, Chuang; Li, Xudong; Li, Kang; Yu, Xin; Yao, Wenming; Peng, Fang; Zhang, Qingli; Dou, Renqin; Gao, Jing; Copner, Nigel
Abstract: We report an 879 nm laser diode (LD) end-pumped quasi-three-level 927 nm laser with a Nd:GdYNbO4 mixed crystal for the first time to the best of our knowledge. Comparing the 927 nm laser's performance under 808 nm and 879 nm LD pumping, we find performance enhancement is achieved by using direct 879 nm LD pumping. A maximum output energy of 42 mJ at 10 Hz is obtained in the 879 nm LD pumped 927 nm laser with an optical-to-optical efficiency of 24% and a beam quality factor of M 2 = 1.7. The dependence of output characteristics on the pumping repetition rate is discussed. The average output power at 927 nm reaches 1.13 W at 100 Hz with an optical-to-optical efficiency of 6.5%.